Imaging the Insertion of Superecliptic pHluorin‐Labeled Dopamine D2 Receptor Using Total Internal Reflection Fluorescence Microscopy. Issue 1 (5th January 2015) - Daly, Kathryn M.; Li, Yun; Lin, Da‐Ting
Abstract: A better understanding of mechanisms governing receptor insertion to the plasma membrane (PM) requires an experimental approach with excellent spatial and temporal resolutions. Here we present a strategy that enables dynamic visualization of insertion events for dopamine D2 receptors into the PM. This approach includes tagging a pH‐sensitive GFP, superecliptic pHluorin, to the extracellular domain of the receptor. By imaging pHluorin‐tagged receptors under total internal reflection fluorescence microscopy (TIRFM), we were able to directly visualize individual receptor insertion events into the PM in cultured neurons. This novel imaging approach can be applied to both secreted proteins and many membrane proteins with an extracellular domain labeled with superecliptic pHluorin, and will ultimately allow for detailed dissections of the key mechanisms governing secretion of soluble proteins or the insertion of different membrane proteins to the PM. © 2015 by John Wiley & Sons, Inc.